The effects of ozone oxidative preconditioning on subarachnoid hemorrhage via rat cerebral vasospasm model - (:unkn) unknown (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2021)
Objective: Cerebral vasospasm after subarachnoid hemorrhage (SAH) is a major cause of morbidity and mortality. Inflammation is the major molecular mechanism observed in vasospastic SAH. Ozone (O3) has been used as a therapeutic agent in the treatment of various conditions and diseases for years. The aim of this study was to evaluate the anti-inflammatory effect of ozone oxidative preconditioning (OOP) in a rat model of SAH in order to assess the therapeutic potential of O3 in SAH therapy. Materials and Methods: In the presented study, an experimental in vivo SAH rat model that provided constriction of large cerebral arteries was used. The inflammatory response of cerebral vasospasm after SAH and the effects of OOP were evaluated by comparing the mRNA levels of inflammatory molecules (tumor necrosis factor-alpha, interleukin-1 beta, and intercellular adhesion molecule-1) in the serum samples of rats. Results: The level of inflammatory molecules increased in vasospasm at 12 h, 24 h, and 48 h in the posttreatment groups. However, intraperitoneal OOP decreased the level of inflammatory molecules dramatically. Conclusions: Our study indicated that O3 treatment has potential in the management of inflammation created in a rat SAH model. These findings may inform further studies investigating possible uses of O3 in the treatment of vasospasm.
Keywords: Cerebral aneurysm; inflammation; ozone oxidative preconditioning; subarachnoid hemorrhage; vasospasm model